Impact of MBBS Curriculum on Knowledge, Attitude, and Practices of Organ Donation - Pari Sharma; Ketaki Poorey; Amol Rajendra Gite; Nakul Sharma (Indian Journal of Transplantation)
Introduction: The obstacles in achieving a high organ donation rate in India are multi-factorial and complex. The lack of infrastructure, lack of awareness, common misconceptions and ethical beliefs being some of the common factors. As doctors play a major role in establishing and ensuring smooth functioning of organ donation programme. The importance to assess the future health care professionals about the knowledge, Attitude and Practice regarding organ donation is the basis of our study. The future of health care being the young medical undergraduate students. Methods: A cross sectional study was done amongst the UG medical students from first, second, third and final year. Students were given a structured and validated questionnaire comprising of 30 questions developed on the basis of previous studies. The questionnaires had 4 components. First component comprised the basic information of the student. Second, third and fourth component comprised of relevant questions regarding knowledge, attitude and practice. The data were entered into Excel sheet and analyzed using SPSS software. For the comparison of the mean score of “knowledge,” “attitude,” and “practice,” the ANOVA test was used. Pairwise proportions were compared for all the years using the Marascuilo procedure. Chi-square test was used to explore association between the year of study with knowledge, attitude, and practice. The level of significance was set as 5% (i.e., P < 0.05 was considered statistically significant). Result: A total of 453 undergraduate medical students participated in the study. A total of 216 1st-year students, 97 2nd-year students, 77 3rd-year students, and 63 final-year students were the division of the study population. The response rate for our study was 64.7%. On comparing pairwise (by Marascuilo procedure) each professional year scores of “knowledge” and “attitude,” there was no significant difference seen. There was a significant difference when comparing “practice” for year 1–3 and year 2–3 in practice for organ donation. The Chi-square test indicates a significant association between the year of study and knowledge level. There is no significant difference in attitude levels across different years of study, students with high attitudes remains relatively consistent across different years of study. Conclusion: One of the pillar concept behind organ donation is “life, pass it on” for such a noble cause to function proficiently and smoothly, one of the key elements is the health-care professionals, especially doctors. As future doctors its important to know the ethical, legal and medical aspects of organ donation. On comparing the results obtained from our study with results from other studies it can be concluded that there is still a huge scope for awareness activities and programs to be conducted among the medical students to raise awareness and clear out the myths regarding organ donation, which can further motivate them toward a more positive attitude regarding organ donation.